Enhancement of the methane removal efficiency via aeration for biochar-amended landfill soil cover. (August 2020) - Huang, Dandan; Yang, Luning; Xu, Wenjun; Chen, Qindong; Ko, Jae Hac; Xu, Qiyong
Abstract: Methane (CH4 ) mitigation of biocovers or biofilters for landfills is influenced by the bed material and oxygen availability. The improvement of active aeration for the CH4 oxidation efficiency of biochar-amended landfill soil cover was investigated over a period of 101 days. There were column 1 as the control group, column 2 with biochar amending the soil cover, and column 3 with daily active aeration besides the same biochar amendment. All groups were inoculated with enriched methane oxidation bacteria (MOB). The average CH4 removal efficiency was up to 78.6%, 85.2% and 90.6% for column 1, 2, and 3, respectively. The depth profiles of CH4 oxidation efficiencies over the whole period also showed that the stimulation of CH4 oxidation by biochar amendment was apparent in the top 35 cm but became very faint after two months. This probably was due to the rapid depletion of nitrogen nutrition caused by enhanced methanotrophic activities. While through aeration, CH4 oxidation efficiency was further improved for column 3 than column 2. This enhancement also lasted for the whole period with a reduced decline of CH4 oxidation. Finally, the major MOB Methylocystis, commonly found in the three columns, were most abundant in the top 35 cm for column 3. A more balanced ratio of MOB and more homogeneous microbial community structures across different soil depths were also the results of active aeration. Graphical abstract: Image 1 Highlights: Active aeration was operated for biochar-amended landfill soil cover (LSC). Average CH4 removal efficiency was 90.6% for biochar-amended and aerated LSC. Active aeration enhanced and prolonged the stimulation of biochar amendment. Active aeration resulted in more abundant and balanced MOB in the top 35 cm.